Sustained Blood Pressure–Lowering Effect of Aliskiren Compared With Telmisartan After a Single Missed Dose. Issue 1 (9th October 2012) - Düsing, Rainer; Brunel, Patrick; Baek, InYoung; Baschiera, Fabio
<x xml:space="preserve">Abstract</x> Poor adherence to antihypertensive drug treatment is common and is often associated with marked prolongations of the dosing interval. Hence, selecting a treatment that has the potential to provide a sustained blood pressure (BP)–lowering effect is important. The objective of this analysis is to compare the sustained efficacy of aliskiren with telmisartan after a single missed dose. This is part of a 12‐week double‐blind study conducted in patients with mild to moderate hypertension randomized to once‐daily aliskiren 150 mg or telmisartan 40 mg for 2 weeks, force‐titrated to double the doses for 10 weeks, followed by placebo for 1 week. The changes in BP from the end of active treatment (EOA) to 48 hours after treatment withdrawal (day 2) were analyzed. Demographic and baseline characteristics were comparable between the treatment groups. Aliskiren continued to show significantly greater reductions in mean sitting systolic BP (−0.7 vs +1.3 mm Hg; P<.05), 24‐hour mean ambulatory systolic BP (−3.6 vs +2.6 mm Hg; P<.01), and 24‐hour mean ambulatory diastolic BP (−3.7 vs +0.4 mm Hg; P<.01) compared with telmisartan from EOA to day 2, despite the similar BP reductions from randomization to EOA. In conclusion, aliskiren sustained the BP‐lowering efficacy better than telmisartan after a single missed dose.